Perancangan Website Sekolah pada SDN 103 Kabupaten Sinjai sebagai Salah Satu Sarana Pembelajaran Online dan Penyajian Informasi - Nahlah, Nahlah; Amiruddin, Amiruddin; Amansyah, Farida (Politeknik Negeri Ujung Pandang, 2017)
The existence of school's website is a necessity that can not be avoided anymore. School's website is very useful as one of online learning and information presenting medium and also as a prerequisite for some inter-schools competition. Without the school's website, a school can not be a winner in a particular competition, like